2022
DOI: 10.1021/acs.jmedchem.2c01818
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight of Synthesized 1,4-Dihydropyridines as an Antidiabetic Sword against Reactive Oxygen Species

Abstract: The pharmacologically privileged DHP derivatives were synthesized using the pragmatic multicomponent Hantzsch synthesis to screen the antidiabetic activity. Initially, the candidates were screened using an in vivo blood glucose test, where compound 8b showed the most prominent antidiabetic effect (% potency = 218%) compared to glimepiride. Then, a propositioned structure–activity relationship study was executed to reveal that longer side chains decreased the DHP’s antidiabetic action. Mechanistically, compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is worth noting that none of the tested isoquinolinones showed an appreciable cytotoxicity against the healthy cell line COS-7 (see Table S3 in the ESI†) nor any toxicity when administered in vivo . We have discussed the relationship between diabetes and inflammation, so biochemical related parameters (like TNF-α and IL-6) 44 after administration of 10f will be quantified in future works.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that none of the tested isoquinolinones showed an appreciable cytotoxicity against the healthy cell line COS-7 (see Table S3 in the ESI†) nor any toxicity when administered in vivo . We have discussed the relationship between diabetes and inflammation, so biochemical related parameters (like TNF-α and IL-6) 44 after administration of 10f will be quantified in future works.…”
Section: Resultsmentioning
confidence: 99%
“…Sidhom et al have synthesized 1,4-dihydropyridine derivatives and screened them using an in vivo blood glucose test. It was reported that compound D showed the most prominent antidiabetic effect with a potency of 218%, compared to glimepiride . Niaz and co-workers identified an antidiabetic (compound E ) with potent inhibitory activity against yeast α-glucosidase with an IC 50 value of 35 ± 0.17 μM, in comparison with the standard drug acarbose (IC 50 = 937 ± 1.60 μM) .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that compound D showed the most prominent antidiabetic effect with a potency of 218%, compared to glimepiride. 21 Niaz and co-workers identified an antidiabetic (compound E) with potent inhibitory activity against yeast αglucosidase with an IC 50 value of 35 ± 0.17 μM, in comparison with the standard drug acarbose (IC 50 = 937 ± 1.60 μM). 22 Moreover, acridinedione derivative (compound F) has the ability to activate and upregulate GPR40 protein expression, which can enhance insulin sensitivity by improving glucose consumption by the liver and muscle tissues and stimulate insulin secretion through a GPR40-PPAR-PI3K/Akt-GLUT4 signaling mechanism.…”
Section: Introductionmentioning
confidence: 99%